Optimizing Gypsum Levels for Amelioration of Sodic Soils to Enhance Grain Yield and Quality of Rice (Oryza sativa L.) - and Sanjay Arora, Y.P. Singh, Ranbir Singh, D.K. Sharma, V.K. Mishra (Journal of the Indian Society of Soil Science, 2016)
Field experiment was conducted on a fine loamy, mixed, hyperthermic, highly sodic soil having pH (10.5), electrical conductivity (EC) (2.42 dS m-1), exchangeable sodium percentage (ESP) (89.0), organic carbon (OC) (0.80 g kg-1) and available nitrogen (94 kg ha-1) to determine the response of two rice (Oryza sativa L.) varieties (CSR 13 and Pant 4) to gypsum levels [(control, 15, 25 and 50% gypsum requirement (GR)]. The study revealed that all the growth parameters (plant height, number of tillers, dry matter accumulation, number of leaves/hill, leaf weight/hill and leaf area index), yield attributes (length of panicle, number of grains/panicle, test weight) and yields (biological yield, straw yield and grain yield) significantly increased with increasing doses of gypsum. Application of gypsum at 50% GR (15.4 t ha-1) was significantly superior over the control and 15% GR doses but at par with that of 25% GR. Significant reduction in soil pH (10.50 to 8.91), EC (1.43 to 0.48 dS m-1) and ESP (89 to 28.5) and increment in OC (0.8 to 1.2 g kg-1) and available N (94 to 190 kg ha-1) were recorded after three years of study with 50% GR level. Grain quality of rice in terms of N content in grain, grain length, length:breadth ratio, brown rice recovery, milled rice recovery, head rice recovery and gel consistency were higher with 50% GR as compared to control but statistically at par with that of 25% GR. There were significant varieties × gypsum interactions on number of effective tillers, dry matter accumulation, number of leaves/hill, leaf weight, number of panicles m-2, length of panicle, number of grains/panicle, test weight and grain yield indicating that the varieties responded to gypsum differently. Variety ‘CSR 13’ showed significant increase over ‘Pant 4’ in all the growth parameters and yield attributes except length of panicle.